Swelling of the Polyester-resins by Sorption with Reference to Water, NaCl, Cu(II) and Urea Solution as Swelling Agents - Narkhede, B.N.; Rathod, S.D.; Munde, A.S.; Chavan, F.R. (Asian Journal of Chemistry, 2010)
Series of polyester-resins prepared by partially esterifying poly (vinyl alcohol) (PVA) with different acid chlorides, such as terephthalic (TPA), isophthalic (IPTA), salicylic (SAA) and p-hydroxybenzoic (Hb) acid chlorides. Swelling of these products in water, dilute solutions of NaCl, copper sulphate, i.e., Cu(II) and urea have been studied. The solubilities (g/mL) and swelling degree (g/g) with reference to above solvents as swelling agents were calculated. Also the degree of salting out of the polyester-resin from NaCl and Cu(II) solutions was calculated. Increase in hydrophilic groups increases swellable sites and hence swellability of the products. It was observed that salt was not sorbed by the resin during the sorption process and the presence of salt lowers the degree of swelling and solubility of the polyester-resins.